(untitled) (Homoeopathy for All, 2023)
The impact of the COVID-19 pandemic has continued for more than 2 years now, and cases are still being reported from different parts of the world due to the emergence of new variants like Omicron. Simultaneously, long COVID, defined as prolonged symptoms after the resolution of COVID-19 infection1, has been a concern for healthcare systems. Since the symptoms of long COVID are diverse and underlying mechanisms are not very clear, a standard treatment to combat its manifestations does not exist. While dependency on bronchodilators and beta blockers exists with variable results, the public has been moving towards using safer alternative therapies that could build resilient body systems and strengthen them internally.